Cerasorb® for filling critical peri-implant defects - Faloni, Ana Paula de Souza; Marques, Daniela Oliveira; Queiroz, Thallita Pereira; Machado, João Paulo Lima; Justo, Yasmin Mayara; Luvizuto, Eloá Rodrigues; Okamoto, Roberta [UNESP]; dos Santos, Pâmela Letícia (Elsevier, 2024)
Objective: Bone loss is a substantial challenge for oral rehabilitation, and immediate implants associated with biomaterials are a treatment option to minimize this condition. This study aimed to assess the repair of peri-implant defects filled with β-tricalcium phosphate. Material and Method: Fifteen rabbits received two osteotomies in each tibia using a 6.1-mm-diameter trephine bur. Next, lance and helical drills were used to prepare the host tissues, and two implants were installed. The defects were filled per groups BC (blood clot) and Ce (Cerasorb®). After 15, 30, and 60 days, the animals were euthanized, and biomechanical, histological, and immunohistochemical analyses were performed. Results: The biomechanical analysis did not show statistical differences intergroup. The morphological analysis showed bone neoformation around Cerasorb® particles and inside their pores only in the regions where the biomaterial was close to the host bone tissue. In all investigated periods, next to the host tissue, there were TRAP-positive osteoclasts in close contact with β-TCP particles, apparently reabsorbing them. However, the biomaterial caused an inflammatory response characterized by several mononucleated cells at 30 days and TRAP-negative multinucleated giant cells at 60 days. Conclusion: Cerasorb® worked as an osteoconductor, considering that regions of bone neoformation were in close contact with the biomaterial around the host tissue.
Keywords: Osteoconduction; Peri-implant defect; TRAP; β-tricalcium phosphate